2018
DOI: 10.1371/journal.ppat.1007416
|View full text |Cite|
|
Sign up to set email alerts
|

STAT6 degradation and ubiquitylated TRIML2 are essential for activation of human oncogenic herpesvirus

Abstract: Aberrations in STAT6-mediated signaling are linked to the development of multiple cancer types. Increasing evidence has shown that activation of human oncogenic herpesvirus lytic replication is crucial for viral tumorigenesis. However, the role of STAT6 in herpesvirus lytic replication remains elusive. Here, by using Kaposi’s sarcoma-associated herpesvirus (KSHV) as a model, we revealed that RTA, the master regulator of lytic replication, interacts with STAT6 and promotes lysine 48 (K48) and K63-linked ubiquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…The results demonstrated that the ubiquitinated STAT6 could be degraded by proteasome and autophagosome–lysosome systems. This finding is consistent with that of the previous reports ( Gu et al, 2018 ) ( Figures 7F,G ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results demonstrated that the ubiquitinated STAT6 could be degraded by proteasome and autophagosome–lysosome systems. This finding is consistent with that of the previous reports ( Gu et al, 2018 ) ( Figures 7F,G ).…”
Section: Discussionsupporting
confidence: 94%
“…The mechanisms of the suppression of STAT6 signaling caused by bixin treatment were further explored. According to previous studies, STAT6 can be degraded via ubiquitin-proteasome system and the lysosomal pathway ( Gu et al, 2018 ). Bixin is recognized as an upstream regulator for P62, a major adaptor protein for autophagy degradation of ubiquitinated protein ( Lin et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2E) (137). Consistent with prolatency functions, STAT6 depletion induced RTA expression and virion production (135,137,138). Notably, IL-4/STAT6 signaling is also reported to induce RTA expression and reactivation of KSHV (139,140), suggesting that full-length STAT6 may be able to activate transcription from the RTA promoter.…”
Section: Stat6mentioning
confidence: 58%
“…After its first isolation from a captive male gibbon [ 3 ], the virus has been recovered from various animal species throughout the world [ 4 7 ]. EMCV is often used as a model to study antiviral immune responses, virus-induced myocarditis and insulin dependent diabetes mellitus [ 8 , 9 ]. However, the mechanisms involved in the internalization and entry of the cardioviruses are still not well elucidated [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%